No promoter left behind (NPLB): learn de novo promoter architectures from genome-wide transcription start sites - Mitra, Sneha; Narlikar, Leelavati (Bioinformatics, 2016)
Promoters have diverse regulatory architectures and thus activate genes differently. For example, some have a TATA-box, many others do not. Even the ones with it can differ in its position relative to the transcription start site (TSS). No Promoter Left Behind (NPLB) is an efficient, organism-independent method for characterizing such diverse architectures directly from experimentally identified genome-wide TSSs, without relying on known promoter elements. As a test case, we show its application in identifying novel architectures in the fly genome.